Contact Pressure Reduction in the Anterior Ankle During Placement of Short Leg Splints. Issue 1 (January 2022) - Farrar, Nicholas; Walley, Kempland C.; Shams, Kameron A.; Mell, Kristopher; Walton, David M.; Holmes, James R.; Talusan, Paul G.
Category: Trauma; Ankle Introduction/Purpose: Lower extremity splints are commonly used in orthopaedic care throughout emergency departments, operating rooms, and outpatient clinics. Although the mainstay of ankle immobilization, they have been associated with ulcers due to high contact pressures over bony prominences and the anterior ankle. High contact pressures may occur in the anterior ankle when splint padding is applied while the ankle is in a plantarflexed position and subsequently dorsiflexed as the plaster or fiberglass hardens. The purpose of this study is to measure contact pressures in the anterior ankle when cast padding is applied in a plantarflexed position and subsequently dorsiflexed. We hypothesized, that the removal of padding over the anterior ankle following dorsiflexion would result in reduced anterior ankle contact pressures. Methods: Short leg posterior U-splints were applied to the right lower extremity in two healthy volunteers with an underlying pressure transducer [Tekscan I-Scan system (Tekscan Inc, South Boston, MA, USA)] on the skin surface centered over the tibialis anterior tendon. Anterior ankle surface pressures were measured when the padding was applied in maximum plantar flexion and dorsiflexed to neutral position as measured by a goniometer. This was then repeated in the same subjects but prior to dorsiflexion, a 3cm x 3cm square of padding was removed over the pressure transducer prior to dorsiflexion. Percent change from initial contact pressure centered on the tibialis anterior with either Webril (Covidien/Medtronic, Dublin, Ireland), or Specialist Cotton Blend Cast Padding (BSN Medical, Charlotte, NC, USA) was calculated. Results: There were 2 limbs analyzed for presentation of this pilot data. The percent change in anterior ankle contact pressure when padding was applied in plantar flexion and then placed in neutral was an average increase of 264% with just padding and 238% with padding and plaster. [TP1] Subsequently, the removal of padding from the anterior ankle resulted in an average decrease of 126% of[TP2] the increased pressure relative to baseline measurements (Figure 1). The reduction in contact force with the removal of Webril was greater than Specialist. Conclusion: In this pilot data, we report increases in anterior ankle contact pressures when splint padding is applied in plantar flexion and re-positioned into neutral. However, removal of anterior ankle padding reduces pressure over the anterior ankle and may reduce the risk of iatrogenic splint related ulcers in this area. Additionally, this technique may elicit varying reductions in anterior ankle pressure depending on the type of cast padding utilized. This data, though preliminary, underscores the importance of avoiding excess padding over the anterior ankle during splint application.